Ekonominių poslinkių pobūdžio Lietuvoje XVIII a. pab. - XIX a. I pusėje klausimu - Pamerneckis, Stasys (Lietuvos istorijos studijos, 1997)
During the first half of the nineteenth century the corvee-works economic system expanded in Lithuania. It involved such inventions as improved agrotechnics, many-field crop-rotation systems, an extension of cattle-breeding, country-estate industry growth, factories and enterprises of spinning, weaving, haberdashery, iron and glass work, leather-ware, etc. All these changes largely increased the incomes of the estates and gave a new life to the economy of Lithuania, although the main part of production was exported to Western countries, and not given to the internal market which was still quite weak. Moreover, these and other improvements in the Lithuanian economy were of mostly quantitative character, orientated towards the increase of incomes by raising the norm of feudal rent which, on the other hand, was based on the peasants' exploitation. The main part of the estates' incomes was invested in the non-production sphere, i.e., luxury items, palace buildings, military troops, etc. Formalised-statistical analysis of Lithuania's serf-estates enabled us to conclude that the components of the inner structure of these estates were faintly balanced; thus, the peasant farms were weakly orientated towards needs of the market. Their economical and growth potential were conditioned by serf-dependence and feudal rent. During the end of the eighteenth century and the first part of the nineteenth century, the commodity-economy predominated in Lithuania. An unreasonable increase of the feudal rent on the basis of the corvee-works system led to a stagnation of the entire agriculture production during the 1850s and 1860s. Qualitative changes within Lithuanian agrarian production, which were closely related to the intensification of capitalistic relationships, started to develop after the abolishment of serfdom in 1861.